2017
DOI: 10.21829/abm121.2017.1177
|View full text |Cite
|
Sign up to set email alerts
|

Riqueza de la familia Orchidaceae en un bosque mesófilo de montaña en Chocamán, Veracruz, México

Abstract: Antecedentes y Objetivos: Existen fragmentos de bosque mesófilo de montaña (BMM) en el centro de Veracruz que no se han estudiado florísticamente. El objetivo de la presente investigación fue registrar la riqueza de orquídeas en un fragmento de este tipo de bosque en Chocamán, Veracruz.Métodos: Se hizo trabajo de recolección de ejemplares, así como revisión de colecciones científicas e información bibliográfica.Resultados clave: El listado incluyó 36 especies pertenecientes a 25 géneros. Epidendrum fue el géne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…First, the locality belongs to the Oaxaca state which has the highest orchid species richness in the country (Soto-Arenas & Salazar 2004, Solano-Gómez et al 2016, but from which only 20 % of its territory has been explored (García-Mendoza 2004). Second, most studies on orchid diversity have been conducted in rainforests and cloud forests (Mejía-Rosero & Pino-Benítez 2009, Focho et al 2010, Allesh et al 2011, García-González & Pérez-Márquez 2011, Gogoi et al 2012a, b, Morales 2012, Gutiérrez 2014, Damian 2015, Nurfadilah 2015, Susan-Tepetlan et al 2015, Castillo-Hernández & Flores-Olvera 2017, Tejeda-Sartorius & Tellez-Velasco 2017; thus, there is a lack of studies addressing the diversity of orchids at temperate forests such as the one found in Santa Catarina Lachatao. Third, the locality is found within the Sierra Norte of the Oaxaca state where the main economic activity is the forestry (Santiago 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the locality belongs to the Oaxaca state which has the highest orchid species richness in the country (Soto-Arenas & Salazar 2004, Solano-Gómez et al 2016, but from which only 20 % of its territory has been explored (García-Mendoza 2004). Second, most studies on orchid diversity have been conducted in rainforests and cloud forests (Mejía-Rosero & Pino-Benítez 2009, Focho et al 2010, Allesh et al 2011, García-González & Pérez-Márquez 2011, Gogoi et al 2012a, b, Morales 2012, Gutiérrez 2014, Damian 2015, Nurfadilah 2015, Susan-Tepetlan et al 2015, Castillo-Hernández & Flores-Olvera 2017, Tejeda-Sartorius & Tellez-Velasco 2017; thus, there is a lack of studies addressing the diversity of orchids at temperate forests such as the one found in Santa Catarina Lachatao. Third, the locality is found within the Sierra Norte of the Oaxaca state where the main economic activity is the forestry (Santiago 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Although orchids are distributed in all ecosystems, most studies on the floristic diversity of this family of plants have been conducted in rainforests and cloud forests (Mejía-Rosero & Pino-Benítez 2009, Focho et al 2010, Allesh et al 2011, García-González & Pérez-Márquez 2011, Gogoi et al 2012a, b, Morales 2012, Gutiérrez 2014, Damian 2015, Nurfadilah 2015, Susan-Tepetlan et al 2015, Castillo-Hernández & Flores-Olvera 2017, Tejeda-Sartorius & Tellez-Velasco 2017. In contrast, fewer studies on floristic diversity of orchids have been conducted in temperate habitats (Cerros-Tlatilpa & Espejo-Serna 1998, Calatayud 2005, Luna-Rosales et al 2007, Huang et al 2008, Rewicz et al 2015.…”
mentioning
confidence: 99%